UKBM in ENHANCING STUDENTS' SCIENTIFIC LITERACY SKILLS on KINGDOM PLANTAE MATERIALS - Eri Wiharni; Mohammad Amin; Sri Rahayu Lestari (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: Biology learning plays an important role in stimulating student literacy skills. This is because biology is the answer to the problems which are related to nature and their interactions with environment. Scientific literacy skills can be imparted to students by using UKBM (Unit Kegiatan Belajar Mandiri or Independent Learning Activity Unit) on Biology. The purpose of this study was to find out the effectiveness of UKBM towards the enhancement of students' scientific literacy skills. The type of this research is quasi-experiment as it is using pretest and post-test question instruments. The statistical data shows that the average value of scientific literacy skills in the experimental class (20.36) is higher than the control class (15.85). The statistical test with Anakova shows an F value is 51,901 with a probability of 0,000 (sig. <0,05) meaning that there is a significant relationship between pretest and post-test scientific literacy skills and the value of F = 10.607 and sig. (0.002) <0.05 indicates that UKBM which is used in learning process is effective to improve students' scientific literacy skills. Abstrak: Pembelajaran biologi berperan penting dalam menumbuhkan keterampilan literasi sains siswa, sebab biologi menjadi solusi permasalahan terkait alam dan interaksinya dengan lingkungan. Keterampilan literasi sains dapat dibekalkan kepada siswa dengan menggunakan UKBM Biologi. Tujuan dari penelitian ini untuk mengetahui keefektifan UKBM terhadap peningkatan keterampilan literasi sains siswa. Jenis penelitian adalah quasi experimental, dengan menggunakan instrumen soal pretes dan postes. Data statistik menunjukan rata-rata nilai keterampilan literasi sains kelas perlakuan (20,36) lebih tinggi daripada kelas kontrol (15,85). Uji statistik dengan Anakova menunjukkan nilai F sebesar 51,901 dengan probabilitas 0,000 (sig.< 0,05) artinya ada hubungan yang signifikan antara pretes dan postes keterampilan literasi sains dan nilai F= 10,607 dan sig.(0,002)< 0,05 artinya bahwa UKBM yang digunakan dalam pembelajaran efektif meningkatkan keterampilan literasi sains siswa